Experimental Investigation of Performance and Emissions of Ethanol and n-Butanol Fuel Blends in a Heavy-Duty Diesel Engine - Han, Jinlin; He, Weiye; Somers, L. M. T. (Frontiers in Mechanical Engineering, 2020)
Alcohol fuels are potential alternative fuels for low temperature combustion concepts in internal combustion engine applications. In this work, 80 vol% of ethanol and 80 vol% of n-butanol are blended with 20 vol% of n-heptane respectively. These two alcohol fuel blends are investigated on a combustion research unit and a single-cylinder heavy-duty engine to compare the combustion and emission characteristics. The effects of EGR rate and achievable operating load range using ethanol and n-butanol are the major goal of this investigation. The results show that the ethanol fuel blend requires much higher temperatures to auto-ignite than the n-butanol blend and diesel do. Both alcohol fuel blends show negligible soot emissions in the medium load range when operated with 40% EGR rate. Yet, the ethanol fuel blend produces more nucleation mode particles and less accumulation mode particles compared to the n-butanol fuel blend under the same operating condition. Furthermore, the particulate size distribution shows that diesel generates more particles with bigger particle diameters, thus more soot mass compared to alcohol fuel blends. Still, both alcohol fuel blends can be operated from low to high load with simultaneous reduction of NOx and soot emissions but at the cost of increased HC and CO emissions. Euro VI regulated soot mass and particle number are achieved from low to medium-high load for alcohol fuels. Diesel poses a great advantage in achieving high combustion efficiency but shows NOx/soot tradeoff at a high EGR rate. Generally, the ethanol fuel blend yields the lowest gross indicated efficiency in the whole test range compared to diesel and n-butanol fuel blend due to the necessity of inlet heating which decreases the thermal efficiency. While the n-butanol fuel blend achieves the highest gross indicated efficiency (above 50%) in the medium-high load range.